Multiple parameter tuning of the bandwidth, wavelength and attenuation of a fiber-based acousto-optic tunable filter - VEERIAH, S; RAHMAN, F; MISHRA, V (ELSEVIER GMBH, 2007)
In this paper we presented a method, which will allow multiple parameter control of the 3-dB bandwidth, center notch wavelength and attenuation level in a fiber-based acousto-optic tunable filter (AOTF). The method basically involves the variation of the interaction length, RF frequency and RF power on a single-fiber device to achieve multiple parameters tuning of the optical filter. The acousto-optic (AO) interaction inside a single-mode fiber (SMF) was studied theoretically and experimentally. (C) 2006 Elsevier GmbH. All rights reserved.